Optimalisasi Peran Layanan Food & Beverage Service Dalam Meningkatkan Kepuasan Tamu di Restoran Suku, Conrad Bali - Mantjari, Josua; Lagarense, Bet El Silisna; Sangari, Fonny (HOSPITALITI DAN PARIWISATA, 2024)
Abstract: This research aims to investigate strategies for optimizing the role of Food and Beverage Service in increasing guest satisfaction at the Suku Restorant, located at Conrad Bali. The research method used is qualitative with a combination of participant observation, in-depth interviews with F&B staff, and analysis of guest satisfaction data. The results showed that increased training, improved internal communications, and improved coordination between different parts of the restaurant had a significant positive impact on the guest experience. An emphasis on responsiveness, friendliness, and expertise in serving food and beverages also plays an important role in improving guest perceptions of service. Recommendations from this research include increasing training of F&B staff in interpersonal and technical skills, implementing an effective internal communications system, as well as implementing best practices in restaurant operational management. By optimizing the role of Food and Beverage Services, it is hoped that a more satisfying environment can be created for guests and increase the reputation of the Suku Restaurant at Conrad Bali.